Multigene typing of Giardia Duodenalis isolated from tuberculosis and non-tuberculosis subjects - Mohammad Rahimi, Hanieh; Javanmard, Ehsan; Taghipour, Ali; Haghighi, Ali; Mirjalali, Hamed (PloS one, 2023)
Giardia duodenalis is a cryptic protozoan, which has eight assemblages (A-H). Assemblages A and B are the main genotypes reported from humans with probable anthroponotic and zoonotic transmission. The current study aimed to characterize G . duodenalis assemblages in tuberculosis (TB) patients and healthy subjects using multilocus genotyping (MLG). Thirty Giardia- positive stool samples, which were obtained from TB patients and healthy subjects were included in the study. After total DNA extraction, three β-giardin (bg) , triosephosphate isomerase (tpi) , glutamate dehydrogenase (gdh) genes were amplified and sequenced. Obtained sequences were compared to the GenBank database to characterize assemblages. Phylogenetic analysis using Maximum Likelihood (ML) and Tamura 3-parameter was performed for each gene. From 30 Giardia- positive subjects, 17 (57%) and 13 (43%) were from healthy and TB-infected subjects, respectively. There was no significant co-existence of Giardia and tuberculosis ( P -value = 0.051). In addition, 14 (46.7%) and 16 (53.3%) of Giardia isolates were from asymptomatic and symptomatic subjects, respectively. PCR amplification was successful in 25 single samples (83.3%) consisted of 20 for tpi , 15 for bg , and 13 for gdh genes. Accordingly, 13/25 (52%) and 8/25 (32%) belonged to assemblage A and assemblages B, respectively, whereas 4/25 (16%) were either assemblage A or B with different genes at the same time. Significant correlation between assemblages and TB, age, and symptoms was not seen. The phylogenetic analyses represented no separation based on TB and gastrointestinal symptoms. Assemblage A was the predominant genotype in samples. The high frequency of assemblage AII indicated importance of anthroponotic transmission of Giardia in both healthy and TB patients. In addition, considering the exclusive reports of sub-assemblage AIII in wild ruminants, the presence of AIII in the current study have to be carefully interpreted. The inconsistency between the assemblage results of either bg or gdh loci with tpi gene signifies the insufficiency of single gene analysis and the necessity for MLG in molecular epidemiology of G . duodenalis .